Theoretically, yes. For lines parallel to y-axis, gradient is zero. Eg, x=4.
Chat with our AI personalities
4x + y + c = 0 or, for a line going through a given point (xo, yo): y + 4x - (xo + yo) = 0 The gradient of a line multiplied by the gradient of a line perpendicular to it is -1; or in other words: The gradient of the perpendicular line is the negative reciprocal of the gradient of the line. Thus: 2x - 8y + 23 = 0 ⇒ 8y = 2x + 23 ⇒ y = 1/4x + 23/8 ⇒ gradient of perpendicular line is -1 ÷ 1/4 = -4 Thus the equation of the perpendicular line to 2x - 8y + 23 = 0 is 4x + y + c = 0. To find the line through point (xo, yo) perpendicular to 2x - 8y + 23 = 0, use the format: y - yo = m(x - xo) ⇒ y - yo = -4(x - xo) ⇒ y + 4x - (xo + yo) = 0
The gradient of a line is the same as the slope of a line. It will tell someone measuring the line how straight the line is.
When equation of line is y=-4x+3, Gradient is -4 (as seen from the coefficient of x) and the y-intercept is +3 (point where x=0)
Gradient = [-4 - 0]/[6 - (-2)] = 4/8 = 0.5 Angle of inclination = arctan(0.5) = 0.464 radians.
L1: y = 1/2*x - 3Gradient of the line = 1/2Negative reciprocal of gradient = -1/(1/2) = -2That is, gradient of perpendicular = -2.This line goes through (0,3),(y - 3) = 2*(x - 0)y - 3 = 2xy = 2x + 3L1: y = 1/2*x - 3Gradient of the line = 1/2Negative reciprocal of gradient = -1/(1/2) = -2That is, gradient of perpendicular = -2.This line goes through (0,3),(y - 3) = 2*(x - 0)y - 3 = 2xy = 2x + 3L1: y = 1/2*x - 3Gradient of the line = 1/2Negative reciprocal of gradient = -1/(1/2) = -2That is, gradient of perpendicular = -2.This line goes through (0,3),(y - 3) = 2*(x - 0)y - 3 = 2xy = 2x + 3L1: y = 1/2*x - 3Gradient of the line = 1/2Negative reciprocal of gradient = -1/(1/2) = -2That is, gradient of perpendicular = -2.This line goes through (0,3),(y - 3) = 2*(x - 0)y - 3 = 2xy = 2x + 3